THE ROLE OF BIG DATA AND LEARNING ANALYTICS IN THE QUALITY ASSURANCE PROCESS OF HIGHER EDUCATION (Education in the 21st Century, 2025)
This research explores how big data and learning analytics can strengthen quality assurance processes in higher education institutions (HEIs). Employing a mixed-methods design, the study gathered data from 600 students and 200 lecturers across six diverse universities, spanning urban and rural contexts. Quantitative analysis, including regression models, showed that engagement with learning management systems (LMS) accounted for 45% of the variation in student grades, underscoring a significant link between technology use and academic outcomes. Qualitative findings from interviews revealed challenges such as inconsistent LMS reliability and ethical issues, notably data privacy concerns, which hinder widespread adoption. The study concludes that learning analytics offer substantial benefits for monitoring and improving educational quality, but their success depends on robust technological infrastructure, staff training, and ethical frameworks. It recommends strategic investments in underserved regions and the establishment of clear data policies to maximize the potential of these tools while addressing equity and privacy.